Multifunctional Agriculture and the Preservation of Environmental Benefits - Werner Hediger; Bernard Lehmann (Swiss Journal of Economics and Statistics, 2007)
We investigate environmental aspects of agriculture from a welfare economic perspective and show that both positive and negative effects exhibit the character of undepletable externalities. To internalise these externalities while taking equity concerns into account, we propose compensation of farmers and forest managers according to the marginal external benefit of their land and a combination of charges and subsidies to improve rural water quality. This is consistent with efficiency requirements, would not cause additional market distortions, and leave the property rights on the land with the farmers while assigning the right on clean air and water to the consumers.
Keywords: D61; Q15; Q24; Q25; Q26; 330; agriculture; externalities; land allocation; multifunctionality; property rights